Analysis of Factors Causing Stunting in Children Under Five and the Role of Socio-Economic Status in Pangkajene and Kepulauan Regency: A Systematic Review - Nurhalilah; Rabina Yunus; Rusli, A.M (Journal of Public Administration and Government, 2024)
Stunting, a chronic condition of impaired growth and development in children under five, remains a pressing public health concern, particularly in Pangkajene and Kepulauan Regency, Indonesia. This systematic review aims to identify and analyze the factors contributing to stunting among children under five and to evaluate the role of socio-economic status in its prevalence. Using a structured methodology, peer-reviewed articles published between 2017 and 2024 were sourced from databases such as PubMed, Scopus, and Google Scholar. The findings reveal that stunting is multifactorial, with key determinants including inadequate maternal nutrition, suboptimal breastfeeding practices, poor dietary diversity, limited access to healthcare services, and recurrent infections. Socio-economic status emerged as a critical factor influencing these determinants, as low income and education levels often exacerbate inadequate nutritional intake and healthcare access. This review underscores the importance of multi-sectoral interventions that address socio-economic disparities, improve maternal and child nutrition, and strengthen healthcare services. Insights from this study contribute to evidence-based policy formulation aimed at reducing stunting and improving child health outcomes in the region.